How to support carbon sequestration and recreational potential at the same time - Deutscher, Jan; Smolíková, Jana (Mendelova univerzita v Brně, 2023)
In recent years, planting trees to protect the climate has become very popular both in the world and here in the Czech Republic. The Paris Agreement in December 2015 and the resulting Nationally Determined Contributions significantly supported the need for the creation and improvement of carbon accounting methods for investments into the forest sector. Appropriately chosen and well-executed tree planting offers a natural, ecological, relatively cheap, and above all simple way to reduce the amount of carbon dioxide (CO2) in the atmosphere as well a number of other environmental benefits. One of these benefits is the positive effects on human well-being and landscape aesthetics both of which is commonly utilized to support recreational potential. However, understanding the financial value of environmental benefits (ecosystem functions) of natural ecosystems and woody vegetation has been an ongoing challenge that still limits the full utilization of close-to-nature landscape management up to this day. Here we show how carbon sequestration potential of individual trees can be evaluated which can in return serve as a motivation tool for conscious tree planting in the rural landscape during all steps of decision making process.
Keywords: tree planting; rural landscape; biomass; CO2 concentration